Training on Climate-Smart Agriculture for Sunflower Value Chain in Tanzania - Recha, John W.M.; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Tanzania is the major sunflower producer in the East Africa region. It has a market dominance of 78%, followed by Uganda (21%). It is an important cash crop in Tanzania and has been attributed to the low cost of production relative to other oilseeds. Moreover, sunflower accounts for 35% of oilseeds produced in the United Republic of Tanzania. Sunflower variety grown in Tanzania has been characterized as resistant to drought conditions and low susceptibility to diseases and pests. Sunflower grows well in semi-arid central plateau regions (Singida, Iringa, Dodoma, Njombe and Rukwa), lake region (Mwanza, Kigoma, Mara, Kagera, Geita, Shinyanga, Simiyu), and eastern region (Mtwara, Lindi, Morogoro) of Tanzania. For instance, sunflower is the second most popular crop after maize in Dodoma and Singida, and the latter region produces about 20% of the cash crop. In addition, commercial sunflower is produced by 75% of the households in Singida, and the land allocated is estimated to be 23,4149 hectares. Central regions like Dodoma, Njombe and Rukwa have collectively allocated more than 84,000 hectares